THE INFLUENCE OF VIDEO EDUCATION ON ADOLESCENTS' KNOWLEDGE OF PUBERTY - Herlina; Dwi Susanti (MEDIA ILMU KESEHATAN, 2025)
Background: Adolescence is a period of transition to adulthood marked by physical, psychological, and social changes. Lack of knowledge can lead to anxiety and risky behaviors. Puberty education needs to be provided from an early age, one of which is through video media that is interesting and easy to understand because it presents visual and audio information.Objective: This study aims to determine the influence of video education on adolescents' knowledge about puberty.Methods: This study uses a quantitative approach with quasi experimental (the one group pretest-posttest) method which was carried out at SMP N 2 Sentolo with a population of 128 grade VII students. The sample in this study amounted to 64 class VII respondents who were selected through the stratified random sampling method. The instrument used was a knowledge questionnaire about puberty. Data analysis was carried out univariate and bivariate using the Wilcoxon Signed Rank Test.Results: The results of the study showed that puberty knowledge before being educated using video had good knowledge (46.9%). Then after being given education using video, it increased to good knowledge (96.9). The results of the Wilcoxon Signed Rank Test were obtained with a value of p = 0.000Conclusion: There is an influence of video education on adolescents' knowledge about puberty at SMP N 2 Sentolo